Mortalidade de frangos de corte relacionada aos fatores térmicos e do transporte pré-abate - Canterle, Ygor Caldeira (2018)
The objective of the present study was to evaluate the thermal and transport factors in the mortality of broilers for slaughter. A total of 299 commercial broiler chickens, female, from Cobb and Ross, aged 27 to 34 days, weighting 1.398 kg, were evaluated. The animals came from aviaries from the Southwest of Paraná, which were slaughtered in April and july of 2016. The information for conducting this study was extracted from a database belonging to a private integrating company. The variables analyzed were: number of birds of each batch, mean weight, age, lineage, time of travel, number of loads, transport dead, temperature and relative humidity of the catch, temperature and relative humidity of the air at arrival at slaughter and stocking of birds by aviary. The dry bulb temperature and relative air humidity data obtained from the schedules, dates and regions of origin and destination of the lots were made through the weather station on Dois Vizinhos city. For the statistical analysis of the variables, the generalized linear model with binomial distribution was used through a logistic regression. The results show that the variable that influenced the mortality of the birds was the transport time, and that each increase in unit time increases the chances of death of the animal by 0.0065%. Less time of 10 minutes, provided greater comfort for birds.